"The use of interactive gaming technologies in the organization of preschool education" - Raxmatova Gulnoza Miraliyevna (Zien Journals, 2022)
This article contains theoretical material on innovative game technology for preschool children. The article also contains comments on the effectiveness of using interactive games with children of older preschool age
Keywords: cognitive research; educational training; teaching methods; mental development